Boey Kim Cheng, Arin Alycia Fong, and Justin Chia (Eds), To Gather Your Leaving: Asian Diaspora Poetry from America, Australia, UK and Europe - Jeyam, Leonard (SARE: Southeast Asian Review of English, 2020)
Book Review